Sensory evaluation of cookies formulated with rhizopora propagules flour using 9-point hedonic scale - I Gusti Agung Ayu Hari Triandini; Wiranto Wiranto; I Gde Adi Suryawan Wangiyana (Journal of Agritechnology and Food Processing, 2024)
This research aims to evaluate sensory using a 9-point hedonic scale and different statistical approaches on cookies made from Rhizopora propagule flour. This research used flour made from Rhizopora propagule and wheat flour with varying compositions to make cookies (C1= Rhizophora flour 100% wheat flour 0%, C2 = Rhizophora flour 75% wheat flour 25%, C3 = Rhizophora flour 50% wheat flour 50%, C4 = Rhizophora flour 25% wheat flour 75%). Respondents gave evaluations using a 9-scale hedonic score for the treatments in 4 parameters, including appearance, aroma, taste, and texture. Evaluation scores were analysed using four statistical approaches: Kruskal-Wallis, Freidman, ANOVA-CRD, and ANOVA-RCBD. The results show that different treatments resulted in significantly different respondent evaluation scores. All respondents give evaluation scores higher than the threshold except for C1. This result means that the addition of wheat flour is still needed in Rhizophora cookie production. All treatments have the same evaluation score in appearance treatment, while C3 and C4 treatments have the highest evaluation scores in aroma, taste, and texture. It could be concluded that the potency of Rhizophora flour from its propagule as an ingredient in cookies is confirmed based on sensory evaluation using a 9-point hedonic scale and the ANOVA-RBCD statistical approach.